ISOLATION AND CHARACTERIZATION OF METHANOTROPHIC BACTERIA FROM RICE FIELDS - Iman Rusmana; ALINA AKHADIYA (SEAMEO BIOTROP, 2009)
Methane is a greenhouse gas and has potency to deplete ozone layer. Rice fields are a significantly sources of atmospheric methane. Chemical fertilizers application in rice fields can increase methane emission. Methanotrophic bacteria are unique in their ability to utilize methane as a sole carbon and energy source. This research was successfully isolating and characterizing methanotrophic bacteria from rice fields in Bogor and Sukabumi, West Java, Indonesia. Determination of methane oxidation activity using Gas Chromatography showed that all isolates performed methane oxidation activity. The highest methane oxidation activity was performed by BGM 9 isolate. And DNA amplification of BGM 9 genome was performed single band of mmoX in the size of 500 bp and three bands of pmoA in the size of 1000, 750 and 500 bp respectively